Bullying no! Public policies and the perspective of the sociology and psychology of education to face violence in the school environment (Research, Society and Development, 2022)
The article discusses public policies aimed at confronting bullying at school, taking as its starting point Law n. 13,185/2015. It is noteworthy that the Federal Constitution of 1988 and the Law of Guidelines and Bases of National Education (LDB 9394/1996) already guarantee the integrality of students and the Child and Adolescent Statute (ECA) that protects them as subjects of specific rights. Bullying and its consequences bring harmful consequences to the socio-emotional and educational development of students. The State recognizes bullying as symbolic and psychological violence, which led it to promote specific legislation to deal with this violent act in the school environment. The article is based on official legislation and authors who discuss bullying in the school context. It starts from the idea that the practice of bullying is symbolic and psychological violence and that this negatively impacts the lives of school subjects.